Effect of interleukin (IL)-35 on IL-17 expression and production by human CD4+ T cells - Okada, Kosuke; Fujimura, Takeki; Kikuchi, Takeshi; Aino, Makoto; Kamiya, Yosuke; Izawa, Ario; Iwamura, Yuki; Goto, Hisashi; Okabe, Iichiro; Miyake, Eriko; Hasegawa, Yoshiaki; Mogi, Makio; et al. (PeerJ, 2017)
Background Interleukin (IL)-17 produced by mainly T helper 17 (Th17) cells may play an important destructive role in chronic periodontitis (CP). Thus, anti-inflammatory cytokines, such as IL-35, might have a beneficial effect in periodontitis by inhibiting differentiation of Th17 cells. Th17 differentiation is regulated by the retinoic acid receptor-related orphan receptor (ROR) α (encoded by RORA) and RORγt (encoded by RORC). However, the role of IL-35 in periodontitis is not clear and the effect of IL-35 on the function of Th17 cells is still incompletely understood. Therefore, we investigated the effects of IL-35 on Th17 cells. Methods Peripheral blood mononuclear cells (PBMCs) were sampled from three healthy volunteers and three CP patients and were analyzed by flow cytometry for T cell population. Th17 cells differentiated by a cytokine cocktail (recombinant transforming growth factor-β, rIL-6, rIL-1β, anti-interferon (IFN)-γ, anti-IL-2 and anti-IL-4) from PBMCs were cultured with or without rIL-35. IL17A (which usually refers to IL-17), RORA and RORCmRNA expression was analyzed by quantitative polymerase chain reaction, and IL-17A production was determined by enzyme-linked immunosorbent assay. Results The proportion of IL-17A+CD4+ slightly increased in CP patients compared with healthy controls, however, there were no significant differences in the percentage of IL-17A+CD4+ as well as IFN-γ+CD4+ and Foxp3+CD4+ T cells between healthy controls and CP patients. IL17A, RORA and RORC mRNA expression was significantly increased in Th17 cells induced by the cytokine cocktail, and the induction was significantly inhibited by addition of rIL-35 (1 ng/mL). IL-17A production in Th17 cells was significantly inhibited by rIL-35 addition (1 ng/mL). Discussion The present study suggests that IL-35 could directly suppress IL-17 expression via RORα and RORγt inhibition and might play an important role in inflammatory diseases such as periodontitis.
Keywords: Interleukin-35; Interleukin-17; Periodontitis; Th17; Retinoic acid receptor-related orphan receptor